2006
DOI: 10.1017/s0033291706007264
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of body dysmorphic disorder: a population-based survey

Abstract: Our study shows that self-reported BDD is relatively common and associated with significant morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
237
4
35

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 381 publications
(302 citation statements)
references
References 31 publications
26
237
4
35
Order By: Relevance
“…This preoccupation leads to significant distress and impairment, time-consuming repetitive behaviors (e.g., grooming rituals, mirror checking, reassurance seeking), and marked avoidance (e.g., of social situations). 1 The disorder has an estimated prevalence of approximately 2% in community samples of adults [2][3][4] and is associated with high levels of occupational and social disability, including absenteeism, unemployment, marital dysfunction, and reduced quality of life. [5][6][7] BDD has received little empirical attention in adolescents, which is surprising given that an adolescent onset is reported in 70% of cases, with a mean age of onset around 16 years.…”
Section: Introductionmentioning
confidence: 99%
“…This preoccupation leads to significant distress and impairment, time-consuming repetitive behaviors (e.g., grooming rituals, mirror checking, reassurance seeking), and marked avoidance (e.g., of social situations). 1 The disorder has an estimated prevalence of approximately 2% in community samples of adults [2][3][4] and is associated with high levels of occupational and social disability, including absenteeism, unemployment, marital dysfunction, and reduced quality of life. [5][6][7] BDD has received little empirical attention in adolescents, which is surprising given that an adolescent onset is reported in 70% of cases, with a mean age of onset around 16 years.…”
Section: Introductionmentioning
confidence: 99%
“…BDD is relatively common, with prevalence estimates ranging between 1 -2% in the general population (Rief et al, 2006;Koran et al, 2008;Buhlmann et al, 2010). The symptoms of BDD have been associated with substantial psychiatric comorbidity (Gunstad and Phillips, 2003;Pavan et al, 2008), poor quality of life (Didie et al, 2007) and alarmingly high suicide rates (Phillips et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…As the prevalence of BDD was higher in the interview sample compared to the total sample, at least part of the explanation is probably that women with BDD are more likely to be single. Previous large population studies have reported that individuals with BDD are more frequently divorced or single than individuals without BDD (Rief et al, 2006;Koran et al, 2008). This is not surprising, since the disorder often leads to impaired functioning in relationships, socializing and intimacy (Phillips, 1991).…”
Section: Discussionmentioning
confidence: 97%
“…Women, who are indeed overweight or obese and preoccupied by this, might also reply "yes" to this question, even if they were not suffering from an eating disorder. Rief et al (2006) also excluded all individuals from BDD diagnosis, who reported their body weight as the primary cause of their appearance concern. In the other large German population study, a more specific way of excluding eating disorder was used (Buhlmann et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation